Segregating domain-general from emotional context-specific inhibitory control systems - ventral striatum and orbitofrontal cortex serve as emotion-cognition integration hubs - Zhuang, Qian; Xu, Lei; Zhou, Feng; Yao, Shuxia; Zheng, Xiaoxiao; Zhou, Xinqi; Li, Jialin; Xu, Xiaolei; Fu, Meina; Li, Keshuang; Vatansever, Deniz; Kendrick, Keith M; et al. (bioRxiv, 2020)
Abstract Inhibitory control hierarchically regulates cognitive and emotional systems in the service of adaptive goal-directed behavior across changing task demands and environments. While previous studies convergently determined the contribution of prefrontal-striatal systems to general inhibitory control, findings on the specific circuits that mediate the context-specific impact of inhibitory control remained inconclusive. Against this background we employed an evaluated emotional Go/No Go task with fMRI in a large cohort of subjects (N = 250) to segregate brain systems and circuits that mediate domain-general from emotion-specific inhibition control. Particularly during a positive emotional context, behavioral results showed a lower accuracy for No Go trials and a faster response time for Go trials. While the dorsal striatum and lateral frontal regions were involved in inhibitory control irrespective of emotional context, activity in the ventral striatum (VS) and medial orbitofrontal cortex (mOFC) varied as a function of emotional context. On the voxel-wise network level, limbic and striatal systems generally exhibited highest changes in global brain connectivity during inhibitory control, while global brain connectivity of the left mOFC was less suppressed during emotional contexts. Functional connectivity analyses moreover revealed that negative coupling between the VS with inferior frontal gyrus (IFG)/insula and mOFC varied as a function of emotional context. Together these findings indicated separable domain general systems as well emotional context-specific inhibitory brain systems which specifically encompass the VS and its connections with frontal regions. Competing Interest Statement The authors have declared no competing interest.